The Kurds in Iran : the past, present and future - Yildiz, Kerim; Tayşi, Tanyel B. (Pluto Press, 2007)
This is one of the first comprehensive accounts of the situation of Kurds in Iran. The authors provide an overview of the issues facing Kurds within the country, and the way they have been affected by geo-political changes in Iran's neighbouring states.The book offers a historical overview of Iran's development since WW1 through to the revolution of 1979, the war with Iraq, and the emergent state policy towards its Kurdish population. It provides a thorough critique of Iran's human rights record, especially for minorities and women. Yildiz and Taysi address Iran's relationship with its neighbours and the West, the implications of Ahmadinejad's rise to power and the impact of the Islamic state on human rights. They analyse Iran's prospects for the future and how the resolution of the Kurdish issue in Iran affects the future of the region as a whole as well as Iran's international policy and relations.
"In association with Kurdish Human Rights Project."
Keywords: Kurds -- Iran -- History.; Kurds -- Civil rights -- Iran.; Kurds -- Iran -- Politics and government.; Kurds -- Iran -- Social conditions.; Iran -- Ethnic relations.; Kurdes -- Iran -- Histoire.; Kurdes -- Droits -- Iran.; Kurdes -- Iran -- Conditions sociales.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; HISTORY -- Middle East -- General.; Ethnic relations; Kurds; Kurds -- Civil rights; Kurds -- Politics and government; Kurds -- Social conditions; Iran; History